2014
DOI: 10.1007/s12665-014-3710-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of geothermal systems around the Red Sea

Abstract: The current thermal regime around the red Sea was initiated by a mantle plume beneath Ethiopia, Eretria, Yemen and SW of Saudi Arabia at about 31 Ma before the present. The evolution of the geothermal systems around the Red Sea is coeval to the initial onset of volcanism over the separated land masses (Eritrea, Ethiopia, Djibouti, Yemen, Saudi Arabia and Egypt at 14 Ma. The entire tectono-magmatic activities around the Red Sea gave rise to several geothermal provinces over the continents surrounding the Red Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…These data have been statistically processed and visualized with machine-learning algorithms, in a GIS environment (Graser, 2013). In order to integrate the dataset with further thermal springs in areas where possible lack of recent data was qualitatively observed such as Argentina (Pesce, 2005), Chile (Lahsen et al, 2010), China (Wang, 2008), Iran (Yousefi et al, 2010 Poland (Ciezkowski et al, 1992), Switzerland (Wexsteen, et al, 1988) and Yemen (Chandrasekharam et al, 2015), their geographic location having been georeferenced using the QGIS software (http://www.qgis.org).…”
Section: World Thermal Springs Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…These data have been statistically processed and visualized with machine-learning algorithms, in a GIS environment (Graser, 2013). In order to integrate the dataset with further thermal springs in areas where possible lack of recent data was qualitatively observed such as Argentina (Pesce, 2005), Chile (Lahsen et al, 2010), China (Wang, 2008), Iran (Yousefi et al, 2010 Poland (Ciezkowski et al, 1992), Switzerland (Wexsteen, et al, 1988) and Yemen (Chandrasekharam et al, 2015), their geographic location having been georeferenced using the QGIS software (http://www.qgis.org).…”
Section: World Thermal Springs Datasetmentioning
confidence: 99%
“…About 60% of hydrothermal fluids recorded in the world are in the range 30 °C-70 °C, corresponding to the reservoir's depths in the range of 2-3 km, depending on local/regional geothermal gradients, and on the specific geometry and recharge mechanisms of the underground circulation paths. Below this range of depths, the weight of the overlying rocks significantly decreases porosity and permeability, hindering the onset of well-extended, and spatially Heat flow map (Lucazeau, 2019) with location of (1) thermal springs (yellow dots; after Waring, 1965;Wexsteen, et al, 1988;Ciezkowski et al, 1992;Pesce, 2005;Wang, 2008;Lahsen et al, 2010;Yousefi et al, 2010;Chandrasekharam et al, 2015), ( 2 Frontiers in Earth Science frontiersin.org continuous hydrothermal circuits (Twiss and Moores, 1997). A broad literature also confirmed that vertical permeability may significantly change under the effect of tectonic activity (e.g., among many others, Wang et al, 2016;Brogi et al, 2021): faulting induced by seismic events has been effective in generating thermal springs emissions belonging to hydrothermal systems due to rock fracturing and the availability of feeding groundwaters.…”
Section: Thermal Springs Geodynamic and Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These were later complimented by focused hydrochemical and isotopic studies (Scripps Institute of Oceanography, 1977). Twenty‐five prospects have thus far been deemed to be suitable for electricity generation (Kebede et al, 2020), many of which are associated with Quaternary volcanism (Chandrasekharam et al, 2015; Omenda, 2009). Among these areas, Aluto‐Langano is the only prospect to have ever produced geothermal energy.…”
Section: Status Of Geothermal Energy In Ethiopiamentioning
confidence: 99%
“…African and Arabian countries have an abundance of geothermal energy resources that are not currently utilized for electrical resource delivery. The development of the geothermal systems in these countries is relatively recent and was initiated during the separation of the Arabian-Nubian Shield (ANS) between 31 and 15 Ma [2][3][4][5][6]. The breakup of the ANS activated large-scale volcanic and tectonic activities over the Arabian shield including the present-day countries of Yemen, Egypt, Eritrea, Djibouti, Ethiopia and Kenya [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%